The construction of performance spaces in Bacchylidesʼ Ode 13 (Argos, 2022)
This paper will analyze Bacchylidesʼ ode 13 paying attention to the relation between the poetic ʻIʼ and the audience, in the case of this ode, Aeginaʼs audience. Focus will be placed on a notion of space in which the configuration of metaphorical spaces converges with the literal space of performance. The main assumption is that the poet carries out the construction and configuration of a ritual space, recognizable for the audience. This marks the beginning of a connection between the facts of the historical-mythological past and the present and the performative contexts of the future, highlighting the importance of the instances of re-performance of poetic texts.
Keywords: Bacchylides; performance; re-performance; space